Size of farms and land-labour ratios in the smallholding sector in West Malaysia. - Abdul Halim Ismail, (Universiti Kebangsaan Malaysia, 1973)
This paper examines the size of farms and the land-labour ratios for various types of farms in the smallholding sector in West Malaysia. It has been found that the size of farms in generally small, and the land-labour ratio generally low. It then examines the relationship between the two and finds that generally the land-labour ratio plays a significant role in determining the size of farms.